面向华裔学生的“听说+读写”中文教学模式探析——以印尼共同希望语言学院2023级大专班为例 - Ming Yue (Sinolingua: Journal of Chinese Studies, 2024)
Teaching model is one of the key factors to improve teaching quality. In view of the tendency of the current international Chinese teaching model to focus on structure and knowledge, but not on pragmatics and ability, the Chinese Language and Literature College of Jinan University in China has innovated a set of "listening and speaking + reading and writing" Chinese teaching model. This model focuses on the mutual coordination of "listening and speaking" and "reading and writing", aiming to quickly improve students' Chinese communication ability. This model has been first practiced overseas at the Common Hope Language School in Indonesia. This article mainly introduces the model and the teaching steps of the listening and speaking class in this model, and uses the students' actual grades to demonstrate the feasibility of this teaching model. The study shows that after about 6 months of intensive study in this model, students' Chinese listening and speaking ability has made significant progress. This model helps to improve the listening and speaking ability of Chinese beginners in a short period of time.